Life after death: what happens to your body after you die? - Wilson, Michael (Cham : Springer Nature Switzerland AG ; Chichester : Praxis Publishing, 2022)
Death is not an end - it's a new beginning. After death, all of the molecules that came together to form the living "you" become nutrients for millions of creatures, large and small. Your body becomes the hub of a complex ecosystem of microbes, insects, worms, plants and more. Cheer up! This book shows how you are going to live forever - as components of so many other wonderful creatures. It describes the science behind the remarkable recycling of your body. We begin with lessons about how your body functions, is a collection of valuable nutrients and is a home to millions of microbes. The book goes on to describe the various stages the body passes through as it decomposes following death. The microbes and insects that make use of your tissues are then introduced. Finally, you will learn about the enduring effects that your body will have on the wider biosphere. We are rich in valuable resources that will end up feeding an immense number and variety of other creatures. Inevitably, your body will support the continuation of life on our beautiful planet - this book describes how all this happens.
Register
Slovník
Keywords: smrť; mŕtvola; zmeny posmrtné; autolýza; interakcie hostiteľa a mikroorganizmu; javy ekologické a environmentálne; cyklus životný; príručka